Improvements in walking speed and timed-up-and go performance times in cardiac rehabilitation - Araya Ramírez, Felipe (2020)
Purpose: To determine the effects of 36 exercise-based cardiac rehabilitation (CR) sessions on walking speed, performance times and hemodynamic variables in cardiac patients. A second aim was to determine the reliability of the timed-up-and-go (TUG) test in CR patients. Methods: Forty-seven patients (age = 58.2 ± 11.6 yr., height = 168.6 ± 8.0 cm, weight = 80.3 ± 12.8 kg, BMI = 28.3 ± 4.5 kg/m2) were measured on heart rate (HR), systolic (SBP) and diastolic (DBP) blood pressure, 6-min walking test (6MWT), and TUG at baseline (B), and following 24 (T24) and 36 (T36) CR sessions. The TUG was performed twice interspersed with a 2-min seated resting. One-way repeated measures ANOVA and Fisher’s LSD post hoc test identified significant mean differences. The intraclass correlation coefficient (ICC) and 95% confidence intervals (95%CI) were used to determine the reliability of TUG at B, T24, and T36. Relative change (Δ%) from B to T24 and T36 and from T24 to T36 were computed for TUG and 6MWT. Results: 6MWT distance improved from B (466.4 ± 72.8 m) to T24 (538.3 ± 67.2 m, p ≤ 0.001), and T36 (554.5 ± 69.1 m, p ≤ 0.001), and from T24 to T36 (p = 0.012). 6MWT walking speed improved from B (4.7 ± 0.7 km/h) to T24 (5.4 ± 0.7 km/h, p ≤ 0.001), and T36 (5.6 ± 0.7 km/h, p ≤ 0.001), and from T24 to T36 (p = 0.012). Exertional HR improved from B (100.1 ± 16.7 bpm) to T24 (106.7 ± 20.4 bpm, p ≤ 0.011), and T36 (108.2 ± 18.6 bpm, p = 0.003). Exertional SBP improved from B to T36 (123.6 ± 20.6 vs. 130.8 ± 19.5 mmHg, p = 0.006). TUG performance times improved from B (5.5 ± 1.2 s) to T24 (5.1 ± 0.9 s, p = 0.003), and T36 sessions (4.9 ± 0.7 s, p ≤ 0.001), and from T24 to T36 (p = 0.015, η2 = 25.6). TUG performance speed improved from B (4.1 ± 0.8 km/h) to T24 (4.4 ± 0.7 km/h, p = 0.011), and T36 (4.5 ± 0.6 km/h, p ≤ 0.001), and from T24 to T36 (p = 0.033). Significant reliability coefficients were observed on the TUG (trial 1 vs. trial 2) on time at B (r = 0.91, p ≤ 0.001, 95%CI = 0.83 to 0.95), T24 (r = 0.94, p ≤ 0.001, 95%CI = 0.90 to 0.97) and T36 (r = 0.88, p ≤ 0.001, 95%CI = 0.79 to 0.94). The biggest Δ% in 6MWT occurred from B to T36 (Δ = 20.2 ± 13.4%, p ≤ 0.001), followed by B to T24 (16.8 ± 13.7%, p = 0.015), and from T24 to T36 (3.3 ± 7.9%, p ≤ 0.001). Conclusion: CR patients improved walking speed, TUG performance, exertional HR and SBP following 36 exercise-based CR sessions. A learning effect was observed on the second trial of the TUG.